40 PENAMPILAN BROILER YANG MENDAPATKAN RANSUM MENGANDUNG TEPUNG DAUN KATUK, RIMPANG KUNYIT, DAN KOMBINASINYA - Mide, Muhammad Zain (Teknosains, 2013)
The aim of this research was to study the performance of broiler given ratio containing powders of Souropus androgynous, turmeric tuber, and their combination. Sixty four broiler, day old chick (doc), were randomly assigned in to 16 experimental cages (4 broilers/cage) with the size of 100 cm x 50 cm x 60 cm/cage. The treatment were : T0 = based ration (control), T1 = based rastion + 1 % Suropus androgynus, T2 = based ration + 1 % turmeric tuber, and T3 = based ration + 0,5 % Sauropus androgynus + 0,5 % turmeric tuber.Statistical analysis indicated that addition powder of sauropus androgynus, turmeric tuber, and their combination into the broiler ration did not effect (P>0,05) performances of broiler (feed consumption, daily gain, carcass percentage, abdominal fat percentage, and feed convertion). Conclusion ; Treatment powder of Sauropus androgynus, turmeric tuber, and their combination give the same effect on performance (consumption, daily gain, carcass percentage, abdominal fat percentage, and feed convertion) broiler.Key word : broiler, sauropus andrygenus, turmeric, performanc